Neonatal Ovarian Cyst: Prenatal Diagnosis And Postnatal Laparoscopic Management - Alvarado, Jackelyne (2017)
Ovarian cysts are the most frequent abdominal tumor in the neonatal stage. They can occur from asymptomatic cases topatients with complicated cysts with bleeding; Ascites, hemorrhagic rupture of the cyst, peritonitis and torsion. Prenataldiagnosis using ultrasonography is fundamental for the timely management of patients.There are different treatment alternatives ranging from observation, percutaneous puncture with ultrasound guidance to thelaparoscopic approach that will depend on the pattern and diameter of the cyst, always keeping in mind the preservation ofthe gonads to ensure development in puberty and future fertility.We present the case of a 45-day-old girl who shows the prenatal diagnosis and the appearance of a complex cyst in one ofher ultrasound controls, which is solved laparoscopically.